Concordance between gambling disorder diagnoses in the DSM-IV and DSM-5; Results from the National Epidemiological Survey of Alcohol and Related Disorders - Petry, Nancy M. (Psychol Addict Behav, 2014)
The fifth edition of the Diagnostic and Statistic Manual for Mental Disorders (DSM-5) eliminates the committing illegal acts criterion and reduces the threshold for a diagnosis of gambling disorder to four of nine criteria. This study compared the DSM-5 “4 of 9” classification system to the “5 of 10” DSM-IV system, as well as other permutations (i.e., just lowing the threshold to four criteria or just eliminating the illegal acts criterion) in 43,093 respondents to the National Epidemiological Survey of Alcohol and Related Conditions. Subgroups were analyzed to ascertain if changes will impact differentially diagnoses based on gender, age or race/ethnicity. In the full sample and each subpopulation, prevalence rates were higher when the DSM-5 classification system was employed relative to the DSM-IV system, but the hit rate between the two systems ranged from 99.80% to 99.96%. Across all gender, age and racial/ethnic subgroups, specificity was greater than 99% when the DSM-5 system was employed relative to the DSM-IV system, and sensitivity was 100%. Results from this study suggest that eliminating the illegal acts criterion has little impact on diagnosis of gambling disorder, but lowering the threshold for diagnosis does increase the base rate in the general population and each subgroup, even though overall rates remain low and sensitivity and specificity are high.